Diseases of Forest Trees in India - Causes, Effects and Methods of Prevention - Bagchee, K. (Indian Forester, 1958)
In a technical paper presented to the Sixth Commonwealth Forestry Conference, 1952, Ottawa, Canada, a review was made of the diseases of forest trees of India, of the depredations caused by the attack of fungi, of the investigations in the Forest Research Institute, Dehra Dun, and of the methods of control from the point of view of management and protection ( Bagchee 1952). A summary of work of approximately 25 years ( 1927-1952) was given in that report. In the following pages, the progress of work in India on forest tree diseases during the last five years is discussed.